A Baseline Study of Workaholism, Passion, and Environmental Mastery in the Social Insurance Sector for Military of State-Owned Enterprises (SOEs) in Indonesia - Shafiya Areta; Mirra Noor Milla (Green Publisher Indonesia, 2024)
Working has become a routine for the majority of people worldwide, and workaholism remains a significant topic of discussion. Researchers suggest that workaholism has negative effects that can disrupt life outside of work. Individuals, especially Millennials and Gen Z, often channel their energy and passion into their work. In psychological studies, workaholism can be understood as obsessive work behavior through the concept of passion. Various studies have established a relationship between obsessive passion for work and workaholic behavior. Other studies indicate that individuals with workaholic tendencies tend to have low environmental mastery. This study examines the relationship between workaholism, passion, and environmental mastery. Among 217 employees from PT. XYZ's insurance sector, self-reports were collected using the DUWAS, Passion Scale, and Environmental Mastery scales. Participants included 123 (56%) men and 94 (43%) women. SEM was used to analyze the path between various dimensions. The results showed a significant positive relationship between Environmental Mastery (EM) and Harmonious Passion (HP) (p = 0.000), indicating that higher EM correlates with higher HP. A significant positive relationship was also found between EM and Obsessive Passion (OP) (p = 0.006). However, no significant relationship was found between HP and Working Compulsively (WC) (p = 0.607) or Working Excessively (WE) (p = 1.186). In contrast, OP showed significant positive relationships with both WC (p = 0.004) and WE (p = 0.004). This study is the first to explore these relationships and serves as a reference for intervention programs on workaholism.